Development of public administration with help of social technologies - Hren, L. M.; Grybko, O. V. (Національний технічний університет "Харківський політехнічний інститут", 2022)
The article considers the importance of social technologies that affect, in fact, all aspects of social phenomena, established their cumulative effect, which is expressed in the constant enrichment of social experience, implementation of effective activities (including management), increasing knowledge, skills, strategies, reusability algorithms for solving typical social problems. A number of reasons have been identified for which social technologies in public administration are becoming increasingly important, namely: 1) in the context of social development, under the influence of globalization, digitalization of public life and immanent network socio-economic links social management; 2) the socio-technological tools are growing rapidly, which allows us to hope today for its organic integration into the network of both social and information technologies of any type organizations; 3) the spread of modern information and communication technologies with their ability to influence the mass public consciousness. The results of decentralization reform in Ukraine are considered as an example of strategic changes in the organization of social life and the basis for the use of social technologies in local community management. The conclusion was made about actualization of social technologies' application in public administration, caused by: 1) orientation on optimum forms of social system existence, its efficiency, rationality; 2) the need to create dynamic social systems that are characterized by balanced relations within the system itself and the harmonization of relations with other systems; 3) the need to implement social creativity; 4) social necessity in the planned, projected and managed development of social systems and processes; 5) social necessity in overcoming the spontaneous development of social processes and ensuring their orientation in the field of meeting social needs; 6) the public need for purposeful change and development of social systems and social processes; 7) the social need to reduce the level of social disorder and instability; 8) necessity to use digital instruments in managing social life; 9) the social need to implement the constructive nature of social processes.

У статті розглянуто значення соціальних технологій, які зачіпають, по суті, всі сторони соціальних явищ, встановлено їх кумулятивний ефект, що виражається у постійному збагаченні соціального досвіду, впровадженні ефективних зразків діяльності (зокрема управлінської), нарощуванні багажу знань, майстерності, стратегій, багаторазовому використанні алгоритмів вирішення типових соціальних проблем. Встановлено низку причин, через які соціальні технології в публічному управлінні стають все більш актуальними, а саме: 1) в умовах суспільного розвитку, під впливом глобалізаційних процесів, цифровізації суспільного життя та іманентними йому мережевими соціально–економічними зв'язками, на перший план висувається проблема соціального управління; 2) стрімко зростає соціально–технологічний інструментарій, що дозволяє вже сьогодні сподіватися на органічне вбудовування його в мережу як соціальних, так і інформаційних технологій організацій будь-якого типу; 3) розповсюдження сучасних інфрмаційно-комунікаційних технологій з їх можливостями впливу на масову суспільну свідомість. Розглянуто результати реформи децентралізації в Україні як приклад стратегічних змін в організації суспільного буття та підґрунтя для застосування соціальних технологій в управлінні громадами. Зроблено висновок про актуалізацію застосування соціальних технологій в публічному управлінні, зумовлену: 1) орієнтацією на оптимальні форми буття соціальної системи, її ефективності, раціональності; 2) потребою у створенні динамічних соціальних систем, які характеризуються збалансованістю відносин усередині самої системи та гармонізацією відносин з іншими системами; 3) потребою у реалізації соціальної творчості; 4) соціальною необхідністю в планомірному, прогнозованому та керованому розвитку соціальних систем та процесів; 5) соціальною необхідністю у подоланні стихійного розвитку соціальних процесів та забезпеченні їх спрямованості в галузь задоволення соціальних потреб; 6) суспільною потребою в цілеспрямованій зміні та розвитку соціальних систем та соціальних процесів; 7) соціальною потребою у зниженні рівня соціальної невпорядкованості та нестабільності; 8) необхідність використання цифрових інструментів в управлінні суспільним життям; 9) соціальної потреби у реалізації конструктивного характеру соціальних процесів.
Розвиток публічного управління за допомогою соціальних технологій
Keywords: social technologies; public administration; strategy; new public management; соціальні технології; публічне управління; стратегія; новий публічний менеджмент